Controle das respostas cardiovasculares ao estresse pela neurotransmissão endocanabinóide no núcleo leito da estria terminal em ratos: interação com a via de sinalização receptor NMDA/nNOS/GCs/proteína quinase G e envolvimento do hipotálamo lateral - Souza, Lucas Gomes de (2020)
The bed nucleus of the stria terminalis (BNST) is a structure located in the rostral forebrain, which has been implicated in autonomic, neuroendocrine and behavioral responses during aversive situations. A recent study from our group showed an inhibitory influence of endocannabinoid signaling within the BNST, acting through the local CB1 receptor, in the tachycardia induced by acute restraint stress, but with no effects on the arterial pressure increase and the sympathetic-mediated cutaneous vasoconstriction. Based upon that, one of the objectives of this work was to evaluate the involvement of NMDA glutamatergic receptor and local nitric oxide (NO) signaling in the control of cardiovascular responses to acute restraint stress by BNST endocannabinoid neurotransmission BNST. We observed that CB1 receptor antagonism in the BNST increased the release of nitric oxide (NO) during acute restraint stress. In addition, bilateral microinjection of the selective CB1 receptor antagonist (AM251) into the BNST facilitated the tachycardic response, but with no effects the pressure response and the cutaneous tail temperature drop induced by acute restraint stress. The facilitation of the tachycardic response to acute restraint stress caused by treatment with the selective CB1 receptor antagonist in the BNST was completely abolished after local pretreatment with a NMDA selective glutamatergic receptor antagonist (LY235959), as well as with selective inhibitors of the enzymes neuronal nitric oxide synthase (NPLA) and soluble guanylate cyclase enzyme (ODQ) and protein kinase G (KT5823). Our results suggest that endocannabinoid neurotransmission in the BNST inhibits local glutamatergic neurotransmission via NMDA/nNOS/sGC/protein kinase G signaling; and this mechanism is involved in the control of tachycardiac response to stress. We also assessed the involvement of GABAergic neurotransmission in the lateral hypothalamus (LH) in the control of cardiovascular responses to acute restraint stress by BNST CB1 receptors. Experiments of characterization of LH GABAergic neurotransmission revealed that bilateral microinjection of a selective GABAA receptor antagonist (SR95531) into the LH, but not a selective GABAB receptor antagonist (CGP35348), reduced the tachycardia response to acute restraint stress, but without affecting the pressor responses and the drop in tail skin temperature. These findings indicated that GABAergic neurotransmission in the LH, acting through local GABAA receptors, plays a facilitatory role in the tachycardic response to restraint stress. Evaluation of the participation of LH GABAergic neurotransmission in HL in the control of cardiovascular responses to acute restraint stress by CB1 receptor in BNST revealed that microinjection of the selective CB1 receptor antagonist into the BNST decreased the neuronal activation of LH neurons during acute restraint stress. Besides, facilitation of tachycardia caused by acute restraint stress following microinjection of AM251 into the BNST was abolished by pretreatment with a selective receptor antagonist GABAA (SR95531) in the LH. Finally, we investigated the involvement of CB1 and CB2 receptors in the BNST in innate anxiety and anxiogenic response to acute restraint stress. Analysis of gene expression revealed the expression of both CB1 and CB2 receptors in the anterior and posterior divisions of the BNST. Intra-BNST microinjection of the selective CB1 receptor antagonist (AM251) increased the open arms exploration of the elevated plus-maze (EPM) in naive animals and inhibited the anxiogenic effect observed in the EPM triggered by acute restraint stress. On the other hand, intra-BNST microinjection of a selective CB2 receptor antagonist (JTE907) dose-dependently increased the innate anxiety in the EPM and inhibited the anxiogenic response evoked by restraint. These results indicate that CB1 and CB2 receptors present in the BNST are involved in the control of innate anxiety and anxiogenic responses evoked by stress.